Risk Factor Stratification for Intracranial Stenosis in Taiwanese Patients With Cervicocerebral Stenosis. Issue 12 (December 2015) - Sung, Yueh‐Feng; Lee, Jiunn‐Tay; Tsai, Chia‐Lin; Lin, Chun‐Chieh; Hsu, Yaw‐Don; Lin, Jiann‐Chyun; Chu, Chi‐Ming; Peng, Giia‐Sheun
Abstract : Background: Intracranial stenosis (ICS) is a major determinant of ischemic stroke in Asians. We determined the clinical significance of different risk factors and the role of ICS in Taiwanese patients with varied distributions of cervicocerebral stenosis. Methods and Results: Presence of extracranial carotid stenosis (ECS, ≥70%) and ICS (>50%) was examined in 13 539 patients using ultrasonography and magnetic resonance angiography, respectively. Seven hundred thirty‐three patients with non‐ECS/ICS (n=372), isolated ICS (n=112), isolated ECS (n=121), or combined ECS/ICS (CEIS, n=128) were selected. Prevalence of ischemic stroke in each group was compared, and risk factors for stenosis were determined. The area under the receiver operating characteristic curve for each risk factor was calculated. Prevalence of ischemic stroke was highest in patients with CEIS (odds ratio 15.86; P <0.001), followed in decreasing order by those with isolated ICS (odds ratio 7.16; P <0.001), isolated ECS (odds ratio 1.77; P =0.011), and non‐ECS/ICS. Multivariate logistic regression analysis revealed that hypertension, coronary artery disease, and smoking were risk factors for isolated ECS; hypertension, diabetes mellitus, coronary artery disease, and smoking were risk factors for isolated ICS; and diabetes mellitus, coronary artery disease, and smoking were risk factors for CEIS. Smoking, diabetes mellitus, and coronary artery disease were the greatest contributors to CEIS, isolated ICS, and isolated ECS, respectively. Conclusions: CEIS was associated with higher odds of ischemic stroke compared with isolated ICS and isolated ECS. Smoking and diabetes mellitus, major determinants of CEIS and isolated ICS, should be targeted in therapeutic strategies to reduce the risk of ischemic stroke.